2024
DOI: 10.1071/ib23067
|View full text |Cite
|
Sign up to set email alerts
|

Limited conversations about constrained futures: exploring clinicians’ conversations about life after stroke in inpatient settings

Felicity A. S. Bright,
Nicola M. Kayes,
Andrew Soundy
et al.

Abstract: Background. After a stroke, people can find it challenging to look forward to the future. Hope, a critical resource for recovery, can be threatened and can be supported or diminished through interactions with clinicians. As such, understanding how conversations can support people embarking on life after a stroke is critical. Our study explored how clinicians talk about the future with patients and considered what factors shape how these conversations occur. Methods. This study drew on the Interpretive Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This leaves us with the question of whether it is easier to maintain or instill hope in earlier stages of rehabilitation compared to later stages? A study by Bright et al showed that conversations about the future also seems to be constrained and limited in the inpatient setting poststroke ( 68 ). The study explored how clinicians talk about the future with patients and Bright et al found that these types of conversations were constrained to short-term futures and limited to what aspects of life after stroke were discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leaves us with the question of whether it is easier to maintain or instill hope in earlier stages of rehabilitation compared to later stages? A study by Bright et al showed that conversations about the future also seems to be constrained and limited in the inpatient setting poststroke ( 68 ). The study explored how clinicians talk about the future with patients and Bright et al found that these types of conversations were constrained to short-term futures and limited to what aspects of life after stroke were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bright et al being able to create conversational and relational spaces where people are supported to look into the future with a sense of possibility, hope, and potential is vital for persons to move forward in their lives post stroke. Based on their findings they conclude that, communication must be seen as a core clinical skill and a clinical intervention in its own right ( 68 ).…”
Section: Discussionmentioning
confidence: 99%